Health Status of Natural Mangrove Forest in The Essential Ecosystem Zone Bagek Kembar Sekotong West Lombok - Astika, Leni; Japa, Lalu; Santoso, Didik (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Natural mangrove forest is a part of the essential ecosystem zone (EEZ) Bagek Kembar Sekotong West Lombok. The mangrove forest including the EEZ Bagek Kembar has been used as a destination for eduecotourism in order to introduce mainly mangrove vegetation and others flora and fauna that could found in the EEZ areas. The present of EEZ Bagek Kembar has prominent values for supporting local communities economy. However, numerous activities done in the EEZ can bring some potential effects to the living of biota, including mangrove community. This research was conducted for analysis the health status of natural mangrove forest of the EEZ Bagek Kembar. Density and canopy covering percentage of mangrove vegetation were analyzed for determining the health status of natural mangrove forest in the EEZ bagek Kembar. The density and present covering of mangrove canopy were determined based on the resolution of Minister for the Environment No.201 year of 2004, about Standard Criteria for Mangrove Damage. The results of this research showed there were 6 species from 4 family of mangrove. The six spesies of mangrove were Avicennia marina, Rhizophora apiculata, R. mucronata, R. stylosa, Sonneratia alba dan Xylocarpus granatum. Density of mangrove vegetation was in range of 900-1.900 trees/ha with in overage of 1.411trees/ha (intermediate to good categories) and the covering percentage of mangrove canopy was 83% (dense category). Natural mangrove forest of EEZ Bagek Kembar Sekotong West Lombok was in good health.